2012
DOI: 10.1590/s0101-20612012005000044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest at different times of day on the physical and chemical characteristics of vegetable-type soybean

Abstract: The objective of this study was to evaluate the effect of harvest at different times of day on the chemical and physical characteristics of vegetable-type soybean BRS 267 cultivar, harvested at the R6 stage (seed development) and to compare it with that on the grains harvested at the R8 stage (maturation). The pods of the BRS 267 cultivar were harvested at the R6 stage (at 8:00 AM, 12:00 AM, and 6:00 PM), the color parameters were evaluated, and the grains were analyzed for chemical composition, activity inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
6
0
5
Order By: Relevance
“…There were differences among the breeding lines and growth stages for isoflavone contents (Table 4). As observed by Santana et al (2012), total accumulation of β-glucosides and aglucones, for all lines, increased at 20 and 29%, respectively, from R6 to R8 (Table 4). Berger et al (2008) reported a continuous accumulation of total isoflavones up to maturity for soybean growing at a greenhouse and in the field.…”
Section: Resultssupporting
confidence: 61%
“…There were differences among the breeding lines and growth stages for isoflavone contents (Table 4). As observed by Santana et al (2012), total accumulation of β-glucosides and aglucones, for all lines, increased at 20 and 29%, respectively, from R6 to R8 (Table 4). Berger et al (2008) reported a continuous accumulation of total isoflavones up to maturity for soybean growing at a greenhouse and in the field.…”
Section: Resultssupporting
confidence: 61%
“…Em geral, as leguminosas oleaginosas tendem a perder níveis consideráveis de amido na maturidade (Baud et al, 2002;Hills, 2004), como foi observado nos resultados da Figura 14A. Os teores de amido reportados por Oliveira et al, (2010) (Dornbos & McDonald, 1986;Saravitz et al, 1987;Lowell & Kuo, 1989;Kumar et al, 2007;Santana et al, 2012), assim como em Brassica campestris (Leprince et al, 1990), trigo (Black et al, 1996) e Arabidopsis thaliana (Baud et al, 2002). A sacarose é peça central no metabolismo de carboidratos, sendo a principal forma do transporte de carbono pelo floema para as sementes em desenvolvimento.…”
Section: Massa Específica Foliarunclassified
“…A síntese de rafinose precisa de sacarose e galactinol, que aumentam concomitantemente com a atividade da enzima galactinol sintase, que usa o mio-inositol como substrato (Karner et al, 2004;Handley et al, 1983). Em soja, Santana et al (2012) quantificaram entre 10,3 µg/mg e 16,1 µg/mg de rafinose em R6 e R8, respectivamente; em cultivares dos E.U.A, foram reportados em média 6,9 µg/mg (Saldivar et al, 2011) e em cultivares brasileiros, 7,2 µg/mg (Oliveira et al, 2010 (Castillo et al, 1990).…”
Section: Efeitos Do Counclassified
See 2 more Smart Citations